(3JMaI GdXQaG haGcgI GddWaGs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3EHQGgje ZdGe Gddg Hf GdSfLGQ GdeGQOjfi s)
(3ChdgG (B:s
(3GdMeO ddg Chdi ef MeOg GdMGeOhf hHYO , abO SCdfi HYV ENhGfi Cf CLeY dg aUhdkG JTJed Ydi CdaGX HGQYI hcdeGJ QGFYI jMJGL EdjgG ai GdeMGVQI heG jLQi Hjf GdfGS ef GdeMGhQI s
(3BNQgG (B:s
( (3ef aUd ai GdOYGA dCHi efUhQ GdKYGdHi cJHg Edi GdCejQ bGHhS bhdg (B: (3hdG jYOe GdeYGdi hGdecGQe WdI Hefg hbOQJg hSYg QMeJg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs